Freshwater components and transports in the Fram Strait – recent observations and changes since the late 1990s - E. Hansen; A. Beszczynska-Möller; M. Karcher; A. Mackensen; U. Schauer; B. Rabe (Copernicus Publications, 2009)
We present the late summer distribution and transports of freshwater components in the upper western part of the Fram Strait during 1998, 2004 and 2005. Hydrographic data and and water δ18O values are analyzed to distinguish Atlantic Water, ice melt (SIM) and freshwater removal from ice formation (IFB), and Meteoric Water (precipitation and riverine sources; MW). Concentrations of these water masses are combined with volume transport estimates from an inverse model. The average liquid freshwater transport relative to a reference salinity of 34.92, was 2500 km3/yr or 80 mSv southward, which is at the upper end of values reported in the literature. Our results indicate that not only the region of the continental slope but also parts of the East Greenland Shelf are important for freshwater transports. We estimate the average transports of of MW and IFB to be between 130 to 160 mSv (4100 to 5000 km3/yr) and 60 to 90 mSv (1900 to 2800 km3/yr) southward, respectively. The southward transport of MW was higher in 2005 than in 1998, but was compensated by a higher IFB transport. These differences in transports were associated with stronger southward velocities and the absence of northward velocities over the continental slope and the eastern East Greenland Shelf in 2005. A simulation using the North Atlantic-Arctic Ocean Sea Ice Model (NAOSIM) shows that the high transport of MW in the Fram Strait in 2005 is in agreement with the temporary storage of river water on the Siberian shelf in the mid-1990s, which reached the north of Greenland in 2003. Our results indicate that the accumulation of increased amounts of river water on the shelves is associated with enhanced ice formation.